On The Welfare Benefits of an International Currency - Kannan, Prakash (IMF Working Papers; Working Paper ;, 2007)
Is it beneficial for a country's currency to be used internationally? And, if so, can we quantify the benefit? Since the emergence of the euro, there has been great interest in the consequences of a transfer of the US dollar's premier international role to the euro. Building on recent advancements in the literature on search models of money, this paper presents a novel model-based approach towards assessing the welfare benefits associated with the international use of a country's currency. The welfare gain for the Euro area in having the euro internationally used ranges from 1.7% to 2.1% of consumption.